Current Controlled Current Differencing Buffered Amplifier: Implementation and Applications - Sudhanshu Maheshwari; Iqbal A. Khan (Active and Passive Electronic Components)
A new four terminal current-controlled active element is introduced, where parasitic resistances at two current input ports are controlled leading to the definition of current-controlled current differencing buffered amplifier. Bipolar implementation and as application current-mode band-pass filter circuits are proposed. Simulation results using real device parameters are included, which show device bandwidth of 35 MHz, low total harmonic distortions, and tuning over a wide current range.